2020
DOI: 10.1016/j.margeo.2020.106115
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional controls on Holocene sea ice dynamics and oceanography in Nares Strait, Northwest Greenland

Abstract: Nares Strait is one of three channels that connect the Arctic Ocean to Baffin Bay. Unique sea-ice conditions in the strait lead to the formation of landfast ice arches at its northern and southern ends. These ice arches regulate Arctic sea-ice and freshwater export through the strait and promote the opening of the North Water polynya. The present study addresses the paucity of pre-satellite records of environmental conditions in the Nares Strait area, and aims at reconstructing Holocene sea-ice conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(72 citation statements)
references
References 60 publications
(134 reference statements)
5
67
0
Order By: Relevance
“…Overall, our mineralogical and geochemical data suggest that the period after 5.8 cal ka BP likely corresponds to the progressive establishment of the modern sedimentation in this region but reflect minimal changes consistent with the neoglaciation in our marine record. Nevertheless, Late Holocene changes in Kane Basin were observed in the same sediment sequence (core Kane2B) based on micropaleontological proxies (Caron, Rochon, et al, 2019; Georgiadis et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Overall, our mineralogical and geochemical data suggest that the period after 5.8 cal ka BP likely corresponds to the progressive establishment of the modern sedimentation in this region but reflect minimal changes consistent with the neoglaciation in our marine record. Nevertheless, Late Holocene changes in Kane Basin were observed in the same sediment sequence (core Kane2B) based on micropaleontological proxies (Caron, Rochon, et al, 2019; Georgiadis et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Jennings et al (2019) reported relatively high sedimentation rates and deposition of detrital carbonate until 7.2 cal ka BP, while ice margin retreated, in agreement with our results. Besides, Georgiadis et al () noticed an expanding sea‐ice cover in Kane basin between ~7.5 and 5.5 cal ka BP, which remained important afterward. This extended sea‐ice cover associated to the enhanced southward flow could have triggered an increased detrital sediment input by sea‐ice transport, originating from the north.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could partly explain the presence of sub-ice colonial species such as M. arctica that have developed strategies to mitigate the effect of unfavorable sea-ice microstructure (Krembs et al, 2011). To the north, evidence of instabilities in the Kane Basin ice arch (Georgiadis et al, 2020) at our study site (Caron et al, 2020), and is coherent with the retreat of the Qangattaq ice cap on the Nuussuaq peninsula between c. 2.5 and 1.9 kyr BP (Schweinsberg et al, 2017) and the Greenland ice-sheet margin in Northern Nunatarssuaq between 2.1 and 1.6 kyr BP (Farnsworth et al, 2018), at the transition to a period of significant boreal atmospheric warming that is commonly referred to as the Roman Warm Period (~2.0-1.65 kyr BP, Wanner et al, 2008).…”
Section: F I G U R Ementioning
confidence: 99%